Pemanfaatan Lahan Dengan Sistem Pengolahan Yang Baik Dan Penggunaan Pupuk Organik Untuk Menerapkan Sistem Pertanian Berkelanjutan - Gulo, Namyra Olivia; Lase, Sintikhe Wahyu Arif; Laoli, Darma Sah Tatema; Gulo, Mesyani; Lase, Natalia Kristiani (CV. SINAR HOWUHOWU, 2024)
This Sustainable agriculture is an important approach in facing global challenges such as soil degradation, climate change, and increasing food demand. This study aims to assess the benefits of implementing a good tillage system and using organic fertilizers in improving land productivity and the sustainability of agricultural ecosystems. Planned tillage involves soil and water conservation techniques that can minimize erosion and maintain soil fertility. Meanwhile, the use of organic fertilizers contributes to the improvement of soil structure, increased microorganism activity, and reduced dependence on synthetic chemical fertilizers. This study uses a qualitative method with data obtained from case studies in several agricultural areas that have adopted sustainable practices. The results show that the combination of good land management and the use of organic fertilizers not only increases agricultural yields, but also supports the sustainability of natural resources in the long run. This research is expected to contribute to the development of policies, training programs, and technical guidelines for farmers to realize a more environmentally friendly and efficient farming system.